Game based learning for primary school students on photosynthesis topic / Nur Afiqah Yazid - Yazid, Nur Afiqah (2017)
Game Based Learning (GBL) has a huge potential for effective learning method for primary school students. It is fun and able to motivate students to facilitate learning and increase the storage capacity of what was taught, exercising the mind and intellectual thoughts. Besides improve the knowledge, educational game-like is perfect for students to improve their knowledge and abilities especially for a crucial topic like photosynthesis in science subject. It can be characterized as game innovation for learning and teaching purposes where it helps students to get knowledge while playing the game. This application implemented ADDIE methodology that consists of five phases which are analysis, design, development, implementation and evaluation. In designing and developing phases, this application not only focusing on learning content, but also used a fun play concept with interesting interface that implemented several game elements and learning theories that suitable for primary school students. They can play and learn at the same time as the application provides learning contents that are easy to memorize by the repetition task to get all photosynthesis elements in the game space. From the evaluation that has been done, majority of the students are satisfied by rating the game as very good with 91%. Meanwhile, 7% students agreed that the game is good and 2% is average. The feedback from students has proved that this application helps students to learn photosynthesis better as they agreed that the game not only enjoyable but also help them in learning process. For future work, this application functionality can be extending where it can add more challenges in the game and also to be built in other platform such as mobile application.